Rare but serious cause for hypokalaemia and hypertension - Shah, Hussun-Ara (BMJ Case Rep, 2021)
Adrenocortical carcinoma is a rare tumour but hypertension conversely is very common. We present the case of a woman in her 30s, with poorly controlled hypertension on four antihypertensive agents. She was referred to the accident and emergency department with hypokalaemia. For a year, she had experienced oedema, weight gain, acne, hirsutism and oligomenorrhea. She had a classic Cushingoid appearance and marked striae. Cushing’s syndrome was confirmed biochemically with an abnormal overnight dexamethasone suppression test. She was diagnosed with metastatic adrenocortical carcinoma following CT imaging. This was resected via a right adrenalectomy, nephrectomy and cholecystectomy. She also received mitotane. Unfortunately, she has a terminal prognosis having experienced a recurrence. This case demonstrates the value of a thorough clinical assessment. More importantly, it highlights the need to refer earlier patients under 40 with resistant hypertension to a specialist. Finally, it encourages clinicians to investigate hypokalaemia in the context of hypertension.